2017
DOI: 10.18203/2320-6012.ijrms20172485
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunctions in patients with chronic renal failure

Abstract: Background: Chronic renal failure (CRF), or end-stage renal disease (ESRD), is a progressive, irreversible deterioration in renal function in which the body’s ability to maintain metabolic and fluid and electrolyte balance fails, resulting in the development of clinical symptoms like uraemia or azotemia. Thyroid hormones have an important role in regulating metabolism, development of the kidney, maintenance of water and electrolyte homeostasis, protein synthesis and influencing other hormone function. Tri-iodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
1
1
Order By: Relevance
“…According to our study, in patients with low T3 syndrome, the mean values of TSH in various stages of renal disease are within normal range, values of TSH did not show any linear correlation with GFR. These results correlate with the studies by Pakhle et al, 11 where there was a positive significant correlation was found between the levels of serum creatinine with levels of T3 and TSH.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…According to our study, in patients with low T3 syndrome, the mean values of TSH in various stages of renal disease are within normal range, values of TSH did not show any linear correlation with GFR. These results correlate with the studies by Pakhle et al, 11 where there was a positive significant correlation was found between the levels of serum creatinine with levels of T3 and TSH.…”
supporting
confidence: 92%
“…Excluding 12 hypothyroid patients who have low T4 values, 24 other patients counting to 44% had T4 level below normal and low T3 syndrome (Table 4) In our study the blood urea varied from 64 -177 mg/dl and creatinine levels varied from 3mg -17.2mg/dl, 24 hours urine protein excretion was <1g/day in all the patients. Our results correlated with the other studies conducted by Pakhle et al, 11 were the mean serum creatinine and blood urea levels in the patients were reported to be 6.17±0.78 mg/dl and 94.92±14.36 mg/dl respectively; and Shamsuddin et al 2014, 15 reported mean serum creatinine levels of 5.83±0.69 mg/dl and that of blood urea was reported to be 96.23±12.24 mg/dl. The results were more or less similar to present study suggesting severe kidney dysfunction.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Many studies on thyroid hormone levels in CRF have revealed variable results. Overall prevalence of thyroid dysfunction was reported as 48%, 38.6% and 58% by Pakhle K et al, 10 Khatiwada S et al 11 and Manasa A.S. Gowda et al 12 respectively as compared to 60% in our study. 9.5% of patients with CKD had subclinical hypothyroidism.…”
Section: Discussioncontrasting
confidence: 41%